The Role of HOP in Emerin-Mediated Nuclear Structure - Kituyi, Sarah Naulikha (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2017)
A vital component of the integral nuclear membrane is emerin, a Lamin Emerin and Man1 (LEM) domain protein whose concentration determines the levels of partner proteins that together constitute the structure of the nuclear envelope. Deficiencies in any of these proteins causes the failure of the structure and assembly and disassembly of the nuclear envelope, which disrupts chromosome segregation and nuclear compartmentalization that are both associated with disease. Emerin also localizes in the cytoplasm where it is implicated in the structure of the cytoskeleton via interaction with tubulin and actin and thus its deficiency may equally contribute to the collapse of the cytoskeleton. The Hsp70-Hsp90 organising protein (Hop) functions as a cochaperone for entry of client proteins into the Hsp90 folding cycle. Hop is upregulated in cancer and regulates a number of cell biology processes via interactions with proteins independently of Hsp90. In a previous study using global whole cell mass spectrometry, emerin was shown to be the most significantly down regulated protein in Hop depleted cell lysates. In this current study, it was postulated that emerin interacts with Hop, and this interaction regulates the stability, and level of emerin in the nucleus which impacts on the structure of the nuclear envelope. We used HEK293T cell lines stably expressing shRNA against Hop, emerin and a non-targeting control alongside the over expression of Hop in HEK293 cells to determine the effect of Hop levels on emerin expression and vice versa via Western blotting. The effect of Hop on the localization of emerin was assessed via subcellullar fractionation and confocal microscopy, while the impact on the structure of the nucleus was determined by transmission electron microscopy (TEM). We established that the depletion of Hop using shRNA and the over expression of Hop both result in the proteasomal and lysosomal degradation of emerin. Co-immunoprecipitation assays confirmed that Hop and emerin are in a common complex, which was not dependent on the presence of Hsp90. Loss of Hop or emerin led to a deformation of nuclear structure and a statistically significant decrease in nuclear size compared to control cells and was associated with an increase in the levels of nuclear protein, lamin A-C. Loss of emerin and Hop resulted in increased long term cell survival, but only after restriction of the nucleus when the cells had migrated across a transwell membrane. Taken together, the results obtained suggest that Hop acts as a scaffold for the stabilization of emerin and that the effects of Hop depletion on the structure of the nucleus and long term survival are mediated via the depletion of emerin.
Keywords: Heat shock proteins; Nuclear structure; Nuclear membranes; Cancer -- Treatment; Molecular chaperones; Cytoskeleton; Cytoplasm